Signifikansi Konsep Christian Nurture Menurut Horace Bushnell Bagi Keluarga Kristen - Vardik Vandiano (REAL DIDACHE: Journal of Christian Education, 2020)
Christian Nurture is a Christian parenting concept that is applied in a family setting. The Christian Nurture pattern was introduced by a pastor named Horace Bushnell who lived in the 19th century, he emphasized the importance of a legacy of faith that is passed on to the next generation. In this 21st century, does the family still play a role in guiding children to God? or whether this nurturing task has been delegated to the church so that the clergy are responsible for the development of the faith of the youth. According to Bushnell parents and the church should strive for the development of the faith of young people. Bilangan Research Center (BRC) in its research in 2018 found that parents who become true followers of Christ produce young people who find their purpose in life in God, have fellowship with God, do not easily give up, have big dreams and are confident to achieve the dream. Busnell based the concept of Christian Nurture based on Ephesians 6: 4 "... educate them in the teachings and counsel of God." Furthermore, in Proverbs 22: 6, it says "Educate a young person according to the way that is proper for him, so that at old age he will not deviate from that path." Busnell argues that there is an organic relationship between parents and children, the relationship in question is the role of parents as pillars who guide children to love and know God's commands. Busnell's concept is strengthened by the text quoted from Deuteronomy 7: 9 "Therefore you must know that God, Your God, He is God, a faithful God, who keeps His covenant and loyal love towards those who love Him and keep His commandments, to the thousands of descendants. " And the similar ideas that underlie the concept of Christian Nurture can be seen clearly from the faith Timothy passed down from his family. "Because I am reminded of your sincere faith, which is the faith that first lived in your grandmother Lois and in your mother Eunice and which I am sure lives also in you. (2 Tim. 1: 5). Some of the above texts convinced Busnell that in a parent who is faithful to God there is a life of strength and piety that is properly channeled to the offspring. This research was conducted using a qualitative approach, namely library studies. Through this paper, the author offers a thought about the concept of Christian nurture according to Horace Bushnell in the family sphere.